(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article analyzes the scientific, social, and philosophical interpretations of the concept of reading. The role of reading culture in the consciousness, spiritual and moral values of young people and the development of society is highlighted. The article discusses the stages of historical formation of books, reading culture, writing and reading, and their impact on human spirituality and thinking. Also, the ancient attitude of the people of Uzbekistan to books, the views of great thinkers on reading books, and the development of reading in modern society will be considered. The study substantiates that reading culture is an important factor in human socialization, thinking, and spiritual development.